Survey on quality control of hemodialysis in Wuhan city in 2016 - XIONG Fei; MIN Yong-long; ZHANG Yan-min; HE Da; CHEN Fang (Linchuang shenzangbing zazhi)
Objective To investigate and analyze the data of quality control of hemodialysis units in Wuhan city,and propose countermeasures. Methods The Hemodialysis Quality Control Center of Wuhan city carried out the annual investigation of 40 hemodialysis units,including the centralized endotoxin detection of dialysis water in each hemodialysis unit. Simultaneously,the dialysis quality data of each dialysis unit were collected and analyzed,including vascular access,hemoglobin( Hb),serum albumin( Alb),serum calcium( Ca),phosphorus( P) and parathyroid hormone( PTH),etc. Results Among the 40 hemodialysis units,endotoxin detection in 4 samples reached a set standard in 26 units( 65%),and the rest units exceeded the standard to varying degrees. All units reached the set standard after rectification. The overall catheter ratio was 22. 22%,and 93. 9% of units exceeded the standard. The reaching standard rate of Hb,Alb,Ca,P and iP TH was 54. 69%,81. 08%,65. 24%,41. 17% and 47. 52%,and the average values of them were( 98. 77 ± 5. 91) g/L,( 37. 47 ± 7. 12) g/L,( 2. 22 ± 0. 09) mmol/L,( 1. 77 ± 0. 52) mmol/L,and( 299. 8 ± 156. 43) ng/L respectively. Conclusions The overall level of hemodialysis in Wuhan was similar to that of domestic level,and the quality control of hemodialysis units should be strengthened to further improve the level of hemodialysis in Wuhan.